The marginalised and voiceless children : an in-depth look into psycho-social support in schools - Z., Ntshuntshe; J., Mathwasa (Penerbit Universiti Kebangsaan Malaysia, 2022)
The death of a parent is a traumatic event that has far-reaching consequences for children's lives. Worldwide the number of orphans and vulnerable children has increased, as well as the adversities confronting them. Besides children’s learning schools have become essential for basic human rights. However, recent years have seen an increased emphasis on the provision of psychosocial support for the wellbeing of all children due to the serious consequences orphans and vulnerable children face causing them to miss out on learning. Tertiary institutions in various countries train teachers in Educational Psychology so that they are empowered to give psychosocial support so that they can respond appropriately to the unique challenges faced by vulnerable children in their setting. The purpose of this study was to evaluate the psychosocial support provided to orphans and vulnerable learners in schools. The study used an interpretivist paradigm within a qualitative approach, with semi-structured interviews conducted with four Life Orientation (LO) teachers, two school principals, and two district managers. The data was analyzed thematically. The findings revealed that teachers lacked understanding and expertise in dealing with orphaned learners and were dismissive of the concept of orphaned learners' vulnerability. The study concluded that a variety of factors contributed to the dissonance of support actions, including a lack of coordination and cooperation in the delivery of support to learners. As a result, the study recommends that teachers be trained in how to support orphaned and vulnerable learners and calls for a multi-sectoral integration of stakeholders in the provision of psychosocial support to orphaned and vulnerable learners.